Overvoltage Analysis of Transmission Towers Considering the Influence of Tower-Footing Impedance - Justo de Araujo, Anderson Ricardo [UNESP] (2017)
Lightning is one of the main causes of outages due to backflashover mechanism in power systems. In this context, the tower-footing impedance presents a key role in the overvoltages caused by this phenomenon. Tower-footing impedance is traditionally modelled as a pure resistance, which is a good approximation, at low frequencies. However, the inductance and resistance of the tower-footing impedance strongly depend on the frequency at higher frequencies of the spectrum that is covered by lightning strokes. As such, their frequency dependence must be considered for accurate calculation of transient responses. Using the Vector Fitting technique, the admittance of grounding electrode buried in soil is represented by a lumped parameter circuit. The circuit model can be connected to transient transmission line models which enables the calculation of the voltages at the cross-arms of the tower. This paper shows the influence of tower-footing impedance of vertical electrodes on the overvoltage caused by a lightning striking at the tower top. The analysis will show how the soil characteristics and geometrical parameters affect the overvoltages at a typical transmission tower.